2011
DOI: 10.1002/ijc.26424
|View full text |Cite
|
Sign up to set email alerts
|

Digoxin use and the risk of cancers of the corpus uteri, ovary and cervix

Abstract: Digoxin is a phyto-estrogen capable of inducing hormonal effects. Use has been associated with increased risk of breast cancer, an estrogen-sensitive malignancy. The incidence of corpus uteri (uterus) cancer is also strongly increased with exposure to estrogens. Therefore, we evaluated whether digoxin use might also increase its incidence. In all women in Denmark, we identified digoxin users from 1995 through 2008 using a nationwide pharmacy registry system. Cancer occurrence was obtained from Danish Cancer Re… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
26
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 32 publications
(26 citation statements)
references
References 24 publications
(39 reference statements)
0
26
0
Order By: Relevance
“…Furthermore, digoxin is associated with higher incidence of male breast cancer [42, 43], and lower incidence of prostate cancer [44], both of which are consistent with estrogenic effects on the respective tissues of origin [45, 46]. Perhaps the most compelling evidence comes from another Danish study, which showed a positive association between digoxin use and incidence of uterine cancer (an estrogen-sensitive malignancy), but null associations with incident cancers of the ovary and cervix (which are not strongly affected by estrogen) [47]. …”
Section: Discussionmentioning
confidence: 92%
“…Furthermore, digoxin is associated with higher incidence of male breast cancer [42, 43], and lower incidence of prostate cancer [44], both of which are consistent with estrogenic effects on the respective tissues of origin [45, 46]. Perhaps the most compelling evidence comes from another Danish study, which showed a positive association between digoxin use and incidence of uterine cancer (an estrogen-sensitive malignancy), but null associations with incident cancers of the ovary and cervix (which are not strongly affected by estrogen) [47]. …”
Section: Discussionmentioning
confidence: 92%
“…Risk factors for uterus cancer include obesity (24), a potentially confounding risk factor because it is shared with cardiovascular disease. However, endometrial cancer risk is decreased in smokers (24), and furthermore, no association was seen between uterus cancer and drugs used for angina (3), which argues against the digoxin effect being related to shared risk factors for cardiovascular disease. That current digoxin increased the risk of only the estrogensensitive cancers of the breast and uterus, both approximately 1.3-to 1.5-fold, but not ovary or cervix cancer, supports a mechanism mediated by its effect on the ERs.…”
Section: Digitalis and Cancer Riskmentioning
confidence: 97%
“…Both forms are phyto-estrogens, or plant estrogens. Recent studies have shown that use of digoxin significantly increases the risk of breast and uterus cancer (1)(2)(3). Both cancers are often estrogen sensitive.…”
Section: Introductionmentioning
confidence: 99%
“…Early animal studies indicate that digoxin may bind to estrogen receptors (ER) [1] and have estrogenic effects. In support of this digoxin is a recognized cause of gynecomastia [3], and digoxin use has been associated with increased risk of estrogen-sensitive cancers such as uterus cancer [4].…”
Section: Introductionmentioning
confidence: 99%